Energy expenditure and intake during puberty in healthy nonobese adolescents: a systematic review. Issue 4 (14th September 2016) - Cheng, Hoi Lun; Amatoury, Mazen; Steinbeck, Katharine
ABSTRACT: Background: Puberty is a time of rapid growth and changing energy requirements and is a risk period for obesity. There is little high-quality evidence on the pubertal alterations of energy expenditure and intake, and this has limited our understanding of energy balance during this important life stage. Objective: The purpose of this study was to summarize existing evidence on pubertal energy expenditure and intake in healthy nonobese adolescents. Design: Studies were identified through CINAHL, the Cochrane Library, Embase, MEDLINE, and Web of Science databases up to August 2015. Articles presenting objectively measured data for basal or resting metabolic rate (BMR/RMR), total daily energy expenditure (TDEE), and/or energy intake (EI) for ≥2 categories of puberty were included. Relevant data adjusted for fat-free mass (FFM) also were extracted. Data were dichotomized into prepubertal and pubertal groups and compared through the use of standardized mean differences (SMDs). Heterogeneous study methodologies precluded meta-analysis. Results: The search netted 6770 articles, with 12 included for review. From these, 6 of 9 studies supported significantly higher absolute BMR/RMR during puberty (SMD: 1.10–5.93), and all of the studies favored significantly higher absolute TDEE during puberty (SMD: 0.46–9.55). These corresponded to a 12% difference and an 18% difference in absolute BMR/RMR and TDEE, respectively. Results adjusted for FFM were equivocal, with 3 studies favoring higher (1 significantly) and 3 favoring significantly lower adjusted BMR/RMR during puberty. Only 1 study reported EI, showing 41% and 25% greater absolute intakes in pubertal males and females, respectively. These differences were not significant after adjustment for FFM. Conclusions: Reasonably consistent evidence exists to support higher absolute BMR/RMR and TDEE in pubertal than in prepubertal adolescents. Differences are largely accounted for by FFM, among other potential factors such as growth- and puberty-related hormones. This review argues for further research into hormonal influences on pubertal energy balance and subsequent effects on obesity risk.